When Culture and Biology Collide : Why We are Stressed, Depressed, and Self-Obsessed - Smith, Euclid O. (Book collections on Project MUSE., 2002)
"Why do we do things that we know are bad for us? Why do we line up to buy greasy fast food that is terrible for our bodies? Why do we take the potentially lethal risk of cosmetic surgery to have a smaller nose, bigger lips, or a less wrinkled face? Why do we risk life and limb in a fit of road rage to seek revenge against someone who merely cut us off in traffic? If these life choices are simply responses to cultural norms and pressures, then why did these particularly self-destructive patterns evolve in place of more sensible ones?" "In When Culture and Biology Collide, E.O. Smith explores behaviors that are endemic to contemporary Western society, and proposes new ways of understanding and addressing these problems." "Topics such as drug abuse, depression, beauty and self-image, obesity and dieting, stress and violence, ethnic diversity, and welfare are all used as sample case studies."--Jacket.